Paramedic Judgement, Decision-Making and Cognitive Processing: A Review of the Literature - Meriem Perona; Muhammad Aziz Rahman; Peter O’Meara (2019)
Background Paramedics routinely perform multiple time-sensitive decisions in dynamic environments, often with limited information and equipment. Paramount to patient safety, how paramedics make judgements and decisions within their uncertain environment is important. The primary aim of this review was to identify, examine and synthesise the published literature on how paramedics working in the out-of-hospital environment use judgement and make decisions. Methods Databases Medline, PubMed, CINAHL, Embase were searched and common themes pertaining to paramedic decision-making were identified. Full text original research articles that focussed on how paramedics perform decision-making in the out-of-hospital environment were included. Papers excluded were non-English; those examining emergency medical technicians, nurse- or physician-led ambulances; paramedics operating in hospital or clinic-based environment; and studies of purely paramedic student populations. Data were managed using the ‘preview, question, read, summarise’ approach. Results A total of 362 abstracts and titles were reviewed; six were found to address the research aim. Of those six, four were qualitative in approach, one quantitative and one was mixed-methods. Overall, paramedics displayed the application of subconscious (intuitive) and conscious (analytical) thought processes – consistent with dual-process theory – with experience and formal education influencing factors. Paramedics gathered cues, problem solved, critically analysed, reasoned and displayed aptitude at rapid clinical impressions in critically ill patients with minimal information. Expert paramedics collected, processed and utilised information differently to novices portraying an interconnectedness of conscious and sub-conscious processing. Conclusion Paramedic judgement and decision-making is complex and multifaceted with multiple layers of knowledge interwoven. Implications for practice include better cognitive performance; educational course structure guidance; encouraging implementation of routine reflection and feedback, thus promoting continued improvement and better patient outcomes. Despite its importance, research was lacking.